Operation and control of a hybrid microgrid containing unbalanced and nonlinear loads - Shahnia, Farhad; Majumder, R.; Ghosh, Arindam; Ledwich, G.; zare, F. (Elsevier S.A., 2010)
This paper shows how the power quality can be improved in a microgrid that is supplying a nonlinearand unbalanced load. The microgrid contains a hybrid combination of inertial and converter interfaceddistributed generation units where a decentralized power sharing algorithm is used to control its powermanagement. One of the distributed generators in the microgrid is used as a power quality compensatorfor the unbalanced and harmonic load. The current reference generation for power quality improvementtakes into account the active and reactive power to be supplied by the micro-source which is connectedto the compensator. Depending on the power requirement of the nonlinear load, the proposed controlscheme can changemodesof operation without any external communication interfaces. The compensator can operate in two modes depending on the entire power demand of the unbalanced nonlinear load. The proposed control scheme can even compensate system unbalance caused by the single-phase microsources and load changes. The efficacy of the proposed power quality improvement control and method in such a microgrid is validated through extensive simulation studies using PSCAD/EMTDC software with detailed dynamic models of the micro-sources and power electronic converters.